Alcohol and its contributory role in fatal drowning in Australian rivers, 2002–2012. (January 2017) - Peden, Amy E.; Franklin, Richard C.; Leggat, Peter A.
Highlights: The first population level analysis of alcohol involvement in unintentional fatal river drowning. 40.3% of people aged 18 years or older recorded a BAC ≥0.20%. Known alcohol involvement found to be more likely for victims who drowned as a result of jumping in (χ 2  = 7.8; p < 0.01). Alcohol related river drowning more likely in evening (χ 2  = 7.8; p < 0.01) and early morning (χ 2  = 16.1; p < 0.01) hours. Aboriginal & Torres Strait Islanders overrepresented in alcohol-related river drowning. Abstract: Objective: Examine the prevalence of alcohol and its contributory role in unintentional fatal river drowning in Australia to inform strategies for prevention. Methods: Cases of unintentional fatal river drowning in Australia, 1-July-2002 to 30-June-2012, were extracted from the National Coronial Information System. Cases with positive alcohol readings found through autopsy or toxicology reports were retained for analysis. Discrete analysis was conducted on cases with a Blood Alcohol Content (BAC) of ≥0.05% (0.05 grams of alcohol in every 100 millilitres of blood). Results: Alcohol was known to be involved in 314 cases (40.8%), 279 recorded a positive BAC, 196 (70.3%) recorded a BAC of ≥0.05%. 40.3% of adult victims had a BAC of ≥0.20%. Known alcohol involvement was found to be more likely for victims who drowned as a result of jumping in (χ 2  = 7.8; p < 0.01), identify as Aboriginal and Torres Strait Islander (χ 2  = 8.9; p < 0.01) and drowned in the evening (χ 2  = 7.8; p < 0.01) and early morning (χ 2  = 16.1; p < 0.01) hours. Discussion: The number of people who drown with alcohol in their bloodstream is concerning and challenging for prevention. To assist with the prevention of alcohol related river drowning improved data quality, as well as a greater understanding of alcohol's contribution and consumption patterns at rivers (especially those <18 years of age) is required. Conclusion: Alcohol contributes to fatal unintentional drowning in Australian rivers. Although prevention is challenging, better data and exposure studies are the next step to enhance prevention efforts.